Heterogeneous ice nucleation activity of bacteria: new laboratory experiments at simulated cloud conditions - O. Möhler (Biogeosciences, 2008)
The ice nucleation activities of five different Pseudomonas syringae, Pseudomonas viridiflava and Erwinia herbicola bacterial species and of Snomax™ were investigated in the temperature range between −5 and −15°C. Water suspensions of these bacteria were directly sprayed into the cloud chamber of the AIDA facility of Forschungszentrum Karlsruhe at a temperature of −5.7°C. At this temperature, about 1% of the Snomax™ cells induced immersion freezing of the spray droplets before the droplets evaporated in the cloud chamber. The living cells didn't induce any detectable immersion freezing in the spray droplets at −5.7°C. After evaporation of the spray droplets the bacterial cells remained as aerosol particles in the cloud chamber and were exposed to typical cloud formation conditions in experiments with expansion cooling to about −11°C. During these experiments, the bacterial cells first acted as cloud condensation nuclei to form cloud droplets. Then, only a minor fraction of the cells acted as heterogeneous ice nuclei either in the condensation or the immersion mode. The results indicate that the bacteria investigated in the present study are mainly ice active in the temperature range between −7 and −11°C with an ice nucleation (IN) active fraction of the order of 10−4. In agreement to previous literature results, the ice nucleation efficiency of Snomax™ cells was much larger with an IN active fraction of 0.2 at temperatures around −8°C.